An interesting rare case of double volvulus. (23rd February 2011) - Chittal, R; Harris, D; Patel, A; Goodyear, S; Parkianathan, V
Abstract : A 71-year-old female presented with recurrent sigmoid volvulus. In the current admission, her symptoms were not settling on conservative measures and subsequently went on to have laparotomy. During laparotomy, along with the sigmoid volvulus, there was associated gallbladder torsion. About 500 cases of gallbladder volvulus have been published in literature, however, in our literature search, the authors did not find any similar published case presenting with volvulus involving the gallbladder and the sigmoid colon at the same time. This patient went onto have cholecystectomy and sigmoid colectomy and had a good postoperative recovery and was discharged on the tenth postoperative day. At 6-week postoperative follow-up, she was doing well with no specific concerns.